PENGARUH BIAYA PROMOSI DAN BIAYA DISTRIBUSI TERHADAP PENJUALAN (Suatu Studi pada Perusahaan Manufaktur Sektor Food and Beverage yang Terdaftar di Bursa Efek Indonesia 2012-2016) - Raisya Astari Rasyid; Leny Suzan (Yayasan Azam Kemajuan Rantau Anak Bengkalis, 2018)
Now a days, the competition between companies is getting tighter with the increasingly competitive competition between business actors. In the course of the company is often faced with various problems in maintaining its survival, such as difficulties in increasing sales, increasingly varied consumer tastes, and uncertain economic conditions. Sales become a very important thing for the company, because the value of the profits or losses derived from sales activities become the source that shapes the overall value of the company and determine whether the company can grow and maintain its business activities. This study aims to find out how the cost of promotion and distribution costs affect the sales of food and beverage manufacturing companies listed on the Indonesia Stock Exchange 2012-2016. The population in this study is a food and beverage sector manufacturing company listed on the Indonesia Stock Exchange. Sample selection technique used is purposive sampling and obtained 9 companies with research period in 2012-2016. Data analysis method in this research is panel data regression analysis using software Eviews version 9. The result of t-test shows that promotion cost have a significant positive effect, and distribution cost has a positive significant effect. The result of F test shows that simultaneously promotion cost and distribution cost influence to sales with adjusted R2 equal to 97,7736%. Keywords: promotion cost, distribution cost, sales.